2016
DOI: 10.1038/nm.4172
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine-to-inosine RNA editing controls cathepsin S expression in atherosclerosis by enabling HuR-mediated post-transcriptional regulation

Abstract: Adenosine-to-inosine (A-to-I) RNA editing, which is catalyzed by a family of adenosine deaminase acting on RNA (ADAR) enzymes, is important in the epitranscriptomic regulation of RNA metabolism. However, the role of A-to-I RNA editing in vascular disease is unknown. Here we show that cathepsin S mRNA (CTSS), which encodes a cysteine protease associated with angiogenesis and atherosclerosis, is highly edited in human endothelial cells. The 3' untranslated region (3' UTR) of the CTSS transcript contains two inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
275
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(292 citation statements)
references
References 63 publications
16
275
0
1
Order By: Relevance
“…The RNA editing sites were identified in inverted Alu repeats, which can form perfectly matched dsRNA structure. These results were consistent with a recent report showing that ADAR1, but not ADAR2, is the main RNA editing enzyme for reversely oriented Alu repeats (Stellos et al, 2016). In this study, knockdown of ADAR2 marginally increased RNA editing levels in the 3'-UTR of DHFR.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The RNA editing sites were identified in inverted Alu repeats, which can form perfectly matched dsRNA structure. These results were consistent with a recent report showing that ADAR1, but not ADAR2, is the main RNA editing enzyme for reversely oriented Alu repeats (Stellos et al, 2016). In this study, knockdown of ADAR2 marginally increased RNA editing levels in the 3'-UTR of DHFR.…”
Section: Discussionsupporting
confidence: 94%
“…It is highly possible that miR-92a-3p and miR-92b-3p have the similar role as miR-25-3p, because these miRNAs shares the seed sequence. Beside miRNAs, a recent study revealed that RNA editing within reversely oriented Alu repeats in the 3'-UTR of cathepsin S enables to recuit RNAbinding protein human antigen R to this region, thereby increasing its mRNA stability (Stellos et al, 2016). Further studies are needed to uncover the significance of these factors on DHFR expression.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that ADAR1 enhances the stability of mRNAs by facilitating the recruitment of HuR/ELAVL1 to these mRNAs (8,41). HuR/ELAVL1 is a U-/AU-rich element binding protein, is an established regulator of mRNA stability and potentially binds to ∼26 000 sites across the transcriptome (4244).…”
Section: Resultsmentioning
confidence: 99%
“…1c). The importance of RNA editing in vascular disease was demonstrated in a recent study 18 . We further validated the results obtained from the GTEx data by applying a targeted sequencing approach (microfluidics-based multiplex PCR and deep sequencing; mmPCR–seq) 19 (Supplementary Note 2) to examine 12,871 exonic sites in 672 loci (Supplementary File 2) on independent tissue samples from two individuals (Extended Data Fig.…”
mentioning
confidence: 94%